UJI EFEKTIVITAS EKSTRAK ETANOL DAN METANOL KULIT PISANG KEPOK (Musa acuminata-xbalbisiana) PADA LARVA NYAMUK Aedes aegypti - Selvi Marcellia; Dewi Chusniasih (Jurnal Farmasi Malahayati, 2020)
Dengue fever is caused by Aedes aegypti mosquitoes. Using of synthetic larvicides has been so many impact on resistance and can damage the environment. Therefore, naturl larvaside by using ethanol and methanol extracts from kepok banana peel (Musa acuminata-xbalbisiana) againts the death of larvae of  Aedes aegypti instar III and IV. This research wasexperimental, with concentration of ethanol extract and methanol treatment of 0,5%, 0,75%, 1%, 2,5%, 5%, kontrol positif dan kontrol negatif controls in five replicaions. Larval mortality is calculated after the first 6 hours of death for up to 24 hours. Larvicidal activity data were analyzed with the Kruskal-Wallis test and probit test to find the LC50 value. The results of the study obtained the value of LC50 in ethanol extrack of kepok banana peels at 3,264% and methanol at 2,681%. LT50 values in the best ethanol and methanol extracts were obtained at a concentration of 5% of 12,136 hour and 12,979 hour.